Morality on Trial: Structure and Intelligibility System of a Court Sentence Concerning Homosexuality - Dupret, Baudouin (Qualitative Sociology Review, 2006)
This article analyses the structural organization of a ruling issued by an Egyptian court in the trial known as the “Queen Boat case”, where several people were arrested on the ground of their alleged homosexuality. With the text, and only the text, as data, it aims at making explicit the possibilities open to potential readers of the ruling. The praxiological study of texts constitutes a relatively new domain of inquiry in which texts are considered as produced objects whose intelligibility is structured and organized in a way that provides instructions for the texts’ reading and accounts for their author’s worldview and purposes. The article briefly presents the Egyptian legal and judicial system. Then, through close observation of each of the constitutive elements and organizational features of the ruling, it shows how this text serves as a vehicle for a limited number of possible logical options. In other words, it describes aspects of the practical grammar of written legal adjudication. Finally, in conclusion, some remarks are formulated concerning rulings as instructed reading of cases submitted to judicial review.